The Influence of First Language on Second Language Pronunciation - Septa Aryanika (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Pronunciation in a second language (L2) is often influenced by the first language (L1), which can hinder intelligibility. Indonesian speakers struggle with certain English sounds, such as /θ/ and /ð/, due to their absence in the L1 phonetic system. To identify the influence of L1 on L2 pronunciation in the context of English language learning in Indonesia and propose strategies to reduce negative transfer effects. This qualitative study used a case study approach, involving 9 students from an English club at XYZ School. A pronunciation test was conducted to measure phonetic transfer between L1 and L2. Results show that L1 phonetic transfer causes errors in specific phonemes. Words with higher phonetic complexity are more challenging to pronounce correctly. Negative phonetic transfer and a lack of prosodic training were identified as major obstacles. Context-based and intensive phonetic training significantly improves pronunciation skills. L2 pronunciation errors are strongly influenced by L1, phonetic complexity, and individual experience. Contextual learning and individualized approaches positively impact pronunciation improvement.